2017
DOI: 10.1155/2017/7406278
|View full text |Cite
|
Sign up to set email alerts
|

Nurses and Physicians Attitudes toward Nurse-Physician Collaboration: A Survey from Gaza Strip, Palestine

Abstract: Interprofessional collaboration and teamwork between nurses and physicians is essential for improving patient outcomes and quality of health services. This study examined the attitudes of nurses and physicians toward nurse-physician collaboration. A cross-sectional study was conducted among nurses and physicians (n = 414) in two main referral public hospitals in the Gaza Strip using the Arabic Jefferson Scale of Attitude toward Physician-Nurse Collaboration. Descriptive statistics and difference of means, prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
75
6
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(98 citation statements)
references
References 19 publications
11
75
6
6
Order By: Relevance
“…Nurse‐physician collaboration and teamwork can improve patient outcomes and ease the burden of a busy ED. Increased collaboration results in lower health care cost, increases job satisfaction, and maintains patients' safety (Elsous, Radwan, & Mohsen, ). However, traditionally, the relationship between physicians and nurses is hierarchical and characterized by medical dominance, with nurses viewed as assistants rather than partners in holistic patient care (Boev & Xia, ).…”
Section: Discussionmentioning
confidence: 99%
“…Nurse‐physician collaboration and teamwork can improve patient outcomes and ease the burden of a busy ED. Increased collaboration results in lower health care cost, increases job satisfaction, and maintains patients' safety (Elsous, Radwan, & Mohsen, ). However, traditionally, the relationship between physicians and nurses is hierarchical and characterized by medical dominance, with nurses viewed as assistants rather than partners in holistic patient care (Boev & Xia, ).…”
Section: Discussionmentioning
confidence: 99%
“…According to the studies, patients cared for by baccalaureate nurses had better outcomes and lower rates of mortality . However, although baccalaureate nurses possess more knowledge in leadership, research, evidence‐based practice, and health care management compared with nurses with lower levels of education, physicians often perceive that there these skills make no difference in the total nursing role, or even that baccalaureate nurses are less well versed in the practical tasks (eg, clinical skills) . Many nurses reported communication difficulties with physicians due to the lack of professional recognition and respect.…”
Section: Discussionmentioning
confidence: 99%
“…28 However, although baccalaureate nurses possess more knowledge in leadership, research, evidence-based practice, and health care management compared with nurses with lower levels of education, physicians often perceive that there these skills make no difference in the total nursing role, or even that baccalaureate nurses are less well versed in the practical tasks (eg, clinical skills). 29,30 Many nurses reported communication difficulties with physicians due to the lack of professional recognition and respect. In addition to poor skills and the lack of cooperation with nurses, physicians have reported delayed execution of tasks by nurses as a main cause of conflicts with them.…”
Section: Interpretation In Comparison With the Existing Literaturementioning
confidence: 99%
“…Again, other studies revealed that MDs perceive themselves to be more powerful and competent than nurses (Achilles, 2010;Fagin & Garelick, 2004;Hoffman et al, 2004;Krogstad, Hofoss, & Hjortdahl, 2004). Another study also reported that MDs perceived nurses as their assistants (Elsous et al, 2017). These findings are contrary to the document prepared by Tanzania nursing and midwifery council, which shows that nursing is an independent profession and self-regulated to function in a broader setting (TNMC, 2014).…”
Section: Factors Influencing Doctors Rejecting Nurses' Opinionmentioning
confidence: 93%
“…Collaboration between nurses and medical doctors (MDs) in clinical facilities is a kind of teamwork, which is reported to result into quality healthcare services. On the other hand, lack of collaboration between nurses and MDs increases medical errors and also leads to suboptimal healthcare services (Elsous, Radwan, & Mohsen, 2017); collaboration between nurses and MDs should, therefore, focus on respect, good communication and shared clinical decision power (Elsous et al, 2017).…”
Section: Introductionmentioning
confidence: 99%